(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The aim of this study was to evaluate whether early childhood care visits performed at the Basic Health Units for the first days of life are relevant contexts to diagnose ASD signs. Participants included 13 children, up to 18 months, seven nursing assistants, two nurses and one pediatrician. Professional behaviors of asking questions to the mothers and evaluating the child, as well as the occurrence of social interaction behaviors, language and restricted and stereotyped patterns by the children were evaluated via video recording. Medical issues related to sleep and eating prevailed over neuropsychomotor development, socialization, and language. Regarding professional behaviors, assessing neuropsychomotor development occurred more frequently than assessing language and socialization. During the appointments, children’s social interactions and language were observed. The study suggests that these appointments are relevant contexts for the early identification of the ASD signs, and reformulation of materials and professional training are recommended.